Molecular characterization and functional analysis of Cry toxin receptor‐like genes from the model insect Galleria mellonella. Issue 4 (15th March 2022) - Dutta, Tushar K.; Veeresh, Arudhimath; Phani, Victor; Kundu, Artha; Santhoshkumar, Kodhandaraman; Mathur, Chetna; Sagar, Doddachowdappa; Sreevathsa, Rohini
Abstract: Crystal (Cry) toxins produced from the soil bacterium, Bacillus thuringiensis (Bt), have gained worldwide attention for long due to their insecticidal potential. A number of receptor proteins located on the epithelial cells of the larval midgut were shown to be crucial for Cry intoxication in different insect pests belonging to order Lepidoptera, Diptera and Coleoptera. A beehive pest, Galleria mellonella, serves as an excellent insect model for biochemical research. However, information on the Cry receptor‐like genes in G. mellonella is limited. In the present study, the full‐length sequences of four putative Cry receptor genes (ABC transporter, alkaline phosphatase, aminopeptidase N and cadherin) were cloned from G. mellonella . All these receptor genes were substantially upregulated in the midgut tissue of fourth‐instar G. mellonella larvae upon early exposure (6 h) to a sub‐lethal dose of Cry1AcF toxin. Oral and independent delivery of bacterially‐expressed dsRNAs corresponding to four receptor genes in G. mellonella suppressed the transcription of target receptors which in turn significantly reduced the larval sensitivity to Cry1AcF toxin. As the laboratory populations of G. mellonella develop Bt resistance in a relatively short time, molecular characterization of Cry receptor genes in G. mellonella performed in the present study may provide some useful information for future research related to the genetic basis of Bt resistance in the model insect. Abstract : Cloning and sequencing of four Cry receptors from Galleria mellonella Expression profile of these genes in G. mellonella Induced knockdown of the receptors reduced larval sensitivity to Cry toxin A. oral delivery of Cry toxin in the G. mellonella larvae B. Cry‐induced disruption of midgut epithelium C. Molecular structure of a gut receptor protein ABCC2 that putatively interacted with Cry